Etyka zawodu inżyniera w świetle wybranych kodeksów - Wajszczyk, Piotr (Annales. Etyka w Życiu Gospodarczym, 2013)
The paper attempts to analyse the ethical duties of engineers contained in selected engineeringcodes of ethics and indicates a few problems arising in teaching professional engineering ethicsin technical studies.The codes of ethics under analysis, both Polish and foreign (American), show similaritiesand differences. The author indicates the likely causes of these similarities and differences and suggeststhe need for further research on the development of ethical standards as well as their implementation,application and enforcement. The author discusses teaching ethics based on his own experience and compares a few Americantextbooks used for engineering ethics teaching. The author indicates a lack of necessary teachingmaterials in Polish and the existence of no Polish forum for discussing ethical problems of engineeringin Poland both in the areas of teaching and research.